Socio-Pedagogic Conditions Of Design Origination - Meliksetyan, Gor (Զանգակ հրատ.)
The article discusses the emergence of design as a profession for the sake of Art and Craft connection. As a means of artistic activity, special schools were guided by teaching methods of design and produced the first graduates. Along with its development, design has not only turned into a separate professional activity, but has also begun to have an influence on the art and design culture altogether. Design, being one of the most important areas of national culture, has always been connected with the aesthetic thought development of the given era. The aforementioned directions of art, creativity, and design, as well as their elements, could not be formed and developed outside the given aesthetic system. Such a high level required an appropriate environment, both in one's own country and in countries connected by certain political and socio-pedagogic ties. Both in the entire cultural and aesthetic system, as well as in design, the successes have been very great when the entire aesthetic and artistic thought has been weighed against already recognized problems. It was only about developing a creative approach to work among students, because for a designer who has to create new drawings almost every day, this is simply necessary (Itten I., Iskusstvo formy, 2004, p. 138). In the content of modern artistic education, a large place is given to the profession of designer, which was the main purpose of this article. Intellectually - constructive thinking, planning is only a “cart” that delivers us to the doors of a new reality (Itten I., Iskusstvo cveta, 2004, p. 58).
Keywords: Pedagogy